Energy intake and sources of energy intake in the European Prospective Investigation into Cancer and Nutrition. - Ocké, M; Larrañaga, N; Grioni, S; van den Berg, S; Ferrari, P; Salvini, S; Benetou, V; Linseisen, J; Wirfält, E; Rinaldi, S; Jenab, M; Halkjaer, J; et al. (2009)
OBJECTIVES: To describe energy intake and its macronutrient and food sources among 27 regions in 10 countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. METHODS: Between 1995 and 2000, 36 034 subjects aged 35-74 years were administered a standardized 24-h dietary recall. Intakes of macronutrients (g/day) and energy (kcal/day) were estimated using standardized national nutrient databases. Mean intakes were weighted by season and day of the week and were adjusted for age, height and weight, after stratification by gender. Extreme low- and high-energy reporters were identified using Goldberg's cutoff points (ratio of energy intake and estimated basal metabolic rate <0.88 or >2.72), and their effects on macronutrient and energy intakes were studied. RESULTS: Low-energy reporting was more prevalent in women than in men. The exclusion of extreme-energy reporters substantially lowered the EPIC-wide range in mean energy intake from 2196-2877 to 2309-2866 kcal among men. For women, these ranges were 1659-2070 and 1873-2108 kcal. There was no north-south gradient in energy intake or in the prevalence of low-energy reporting. In most centres, cereals and cereal products were the largest contributors to energy intake. The food groups meat, dairy products and fats and oils were also important energy sources. In many centres, the highest mean energy intakes were observed on Saturdays. CONCLUSIONS: These data highlight and quantify the variations and similarities in energy intake and sources of energy intake among 10 European countries. The prevalence of low-energy reporting indicates that the study of energy intake is hampered by the problem of underreporting.